Pengaruh Kesadaran Wajib Pajak, Sanksi Pajak dan Sistem Samsat Drive Thru terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Kendaraan Bermotor pada Kantor Samsat Bandar Lampung - Dwi Anggraeni Saputri; Nur Anisa (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2020)
This study aims to determine the effect of taxpayer awareness, tax sanctions, and samsat drive thru system on taxpayer compliance in paying motor vehicle tax at the Bandar Lampung Samsat Office. The method of analysis uses multiple linear regression. The population was taken from motorized taxpayers who were registered at the Bandar Lampung Samsat Office. The sample used in this study was 100 respondents and the sampling technique used random sampling. The variables in this study are independent variables, namely taxpayer awareness (X1), tax sanctions (X2) and samsat drive thru system (X3), while the dependent variable is taxpayer compliance (Y). data were analyzed using SPSS. The results showed that the awareness of taxpayers, tax sanctions, and samsat drive thru systems simultaneously had a positive and significant effect on taxpayer compliance in paying motor vehicle tax at the Bandar Lampung Samsat Office.